2010
DOI: 10.1002/jmr.1003
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and structural analysis of interactions between peptide ligands and SEB

Abstract: Staphylococcal enterotoxin B (SEB) is an exotoxin produced by Staphylococcus aureus and commonly associated with food poisoning. In this study, SEB-binding peptides were identified by screening a phage displayed peptide library. The binding of peptides to SEB was tested with isothermal titration calorimetry (ITC) and of the five selected peptides, three showed affinity to SEB, with one measured to have the highest affinity constant (10(5) M(-1)). ITC revealed that the interaction of peptide ligands with SEB wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The binding of SEB to the off‐cell peptide in the peptide‐ELISA was approximately 10‐times greater than the apparent on‐cell K d . The on‐cell versus off‐cell binding affinity differences has also been observed for phage peptides with SEB; high‐affinity samples were identified in phage‐ELISA but did not bind during peptide‐ITC experiments (Dudak et al, ). The specificity difference between on‐cell and off‐cell reagent (Figures , , ) was less disparate than the affinity results (Supplemental Figure 1, Figure 2).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The binding of SEB to the off‐cell peptide in the peptide‐ELISA was approximately 10‐times greater than the apparent on‐cell K d . The on‐cell versus off‐cell binding affinity differences has also been observed for phage peptides with SEB; high‐affinity samples were identified in phage‐ELISA but did not bind during peptide‐ITC experiments (Dudak et al, ). The specificity difference between on‐cell and off‐cell reagent (Figures , , ) was less disparate than the affinity results (Supplemental Figure 1, Figure 2).…”
Section: Discussionmentioning
confidence: 82%
“…Selectivity or specificity of a target capture reagent is as important as binding affinity when detecting samples in a complex matrix. Further complicating the isolation of SEB‐selective reagents using phage is the observed specificity difference between the phage‐ELISA (on‐cell) and the SPR analysis of the identical free peptide (off‐cell), even for high‐affinity phage clones (Soykut et al, ; Dudak et al, ). In this study of bacterial display libraries, we will compare the on‐cell selectivity using a SEB concentration‐dependent flow cytometry method with the selectivity of the synthetic peptide using a peptide‐ELISA method (Kogot et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein interactions with other proteins Protein interactions with small ligands (including co‐factors and drugs) Protein/peptide interactions with metals and ions …”
Section: Introductionmentioning
confidence: 99%
“…However, this study did not involve an examination of the mechanism of the peptide–SEB interaction. Two years later, Dudak et al reported a thermodynamic and structural analysis of the binding interactions between peptide ligands and SEB [ 125 ]. They studied the core amino acids playing an important role in the binding between the peptides and SEB.…”
Section: New Trendsmentioning
confidence: 99%